Books Reviewed Elsewhere (Academy of Management Review, 1980)
This article presents a list of books reviewed in different periodicals, including “Long-Range Forecasting: From Crystal Ball to Computer,” by J.S. Armstrong, which was reviewed in the July 1979 issue of the “Journal of Operational Research Society;” “Management Development in the Organization,” written by D. Ashton and M. Easterly-Smith, which was reviewed in the August 1979 issue of the periodical “Personnel Management;” and “Poverty of Power: Energy and the Economic Crisis,” which was reviewed in the July 1979 issue of the periodical “Economic Development and Cultural Change.